Reading Strategy Patterns in Secondary School Learners: Gender and Cultural Familiarity in Multicultural Texts - Mfanukhona Wonderboy Kunene; Nicholus Nyika (UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
Understanding how learners use reading strategies across culturally familiar and unfamiliar texts is vital for effective literacy instruction, yet gender-related patterns in this context remain underexplored. This study examined gender differences in reading strategy use among 200 senior secondary English as a Second Language (ESL) learners in Manzini, Eswatini. Using a within-subjects quasi-experimental design, participants (114 female, 86 male) read two narrative–descriptive passages differing in cultural familiarity in a counterbalanced order, two weeks apart, and completed the Survey of Reading Strategies (SORS). The passages were matched for length and readability, and the SORS demonstrated excellent internal consistency (αoverall = .94; subscales α = .92–.88). Data were analysed using descriptive statistics, paired-samples t-tests, Welch’s t-tests, Pearson correlations, and effect-size estimates (Cohen’s d). Results showed that girls reported significantly higher use of global and total strategies than boys (Global: t(≈198) = −2.56, p = .011, d = .31; Total: t(≈198) = −2.29, p = .023, d = .32), while no significant gender differences appeared for support or problem-solving strategies. Text familiarity did not significantly affect strategy use (paired tests p > .24), and inter-strategy correlations were minimal (average r ≈ −0.001 to −0.005), indicating largely independent deployment. The findings reveal subtle gendered tendencies and a limited effect of cultural familiarity, underscoring that learners’ strategy orchestration cannot be assumed. Implications call for culturally responsive and gender-sensitive literacy instruction that explicitly scaffolds metacognitive awareness and strategy integration in ESL classrooms.